2022
DOI: 10.1101/2022.07.19.500574
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Mitochondrial genome variation affects humoral and cell-mediated innate immune responses and infection outcomes

Abstract: Mitochondria participate in various cellular processes including energy metabolism, apoptosis, stress responses, inflammation and immunity. While mitochondrial dysfunction contributes to many diseases, mitochondrial perturbations can also be beneficial, a phenomenon coined mitohormesis. We investigated how mitochondrial variation contributes to the heterogeneity of infection outcomes and whether moderate mitochondrial dysfunction could benefit immune-challenged individuals. We took three approaches to model va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 165 publications
0
4
0
Order By: Relevance
“…Recent work on some of the cybrids used in the present work has also found that mitochondrial variation can affect immune deployment directly, by affecting the production of ROS and the proliferation and differentiation of haemocytes during parasitoid wasp infection, particularly in lines with low mitochondrial copy number and non-synonymous substitutions in cytochrome b (OXPHOS complex II) and cytochrome c oxidase subunit 3 (COIII), such as mitotype mtKSA2 [23,50]. In addition, there is some evidence that trade-offs between immunity and fecundity are associated with disruptions in mitochondrial function [22].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Recent work on some of the cybrids used in the present work has also found that mitochondrial variation can affect immune deployment directly, by affecting the production of ROS and the proliferation and differentiation of haemocytes during parasitoid wasp infection, particularly in lines with low mitochondrial copy number and non-synonymous substitutions in cytochrome b (OXPHOS complex II) and cytochrome c oxidase subunit 3 (COIII), such as mitotype mtKSA2 [23,50]. In addition, there is some evidence that trade-offs between immunity and fecundity are associated with disruptions in mitochondrial function [22].…”
Section: Discussionmentioning
confidence: 98%
“…Using a randomized block design, we lightly anesthetized 2-3 day old female flies (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) flies per genotype per treatment for a total of 472 flies) and pricked them in the thorax with a 5mm needle, dipped in an aliquot of heat-killed P. entomophila., or in sterile PBS to control for the effect of pricking.…”
Section: Locomotor Activity and Lifespanmentioning
confidence: 99%
See 3 more Smart Citations